Based blockchain-PSO-AES techniques in finger vein biometrics: a novel verification secure framework for patient authentication - Albahrey, Shihab Ahmed (Tanjong Malim, 2019)
Based blockchain-PSO-AES techniques in finger vein biometrics: a novel verification secure framework for patient authentication by Albahrey, Shihab Ahmed